Dependence of H2O/CO2 Co-Electrolysis Performance of SOEC on Microstructural and Thermodynamic Parameters. Issue 7 (4th May 2016) - Lee, Tae-Ryong; Im, Ha-Ni; Jeon, Sang-Yun; Yoo, Young-Sung; Chavan, Archana U.; Song, Sun-Ju
Abstract : High temperature co-electrolysis of steam and CO2 based on solid oxide electrolysis cell (SOEC) to produce syngas as a feedstock for the well-known Fischer-Tropsch process is the main aim of the present research. Here Ni-8YSZ/8YSZ/LSCF6428-GDC button cells have been fabricated and the effect of the different microstructural parameters like air electrode thicknesses, fuel electrode porosities, adhesion layer and thermodynamic parameters like gas composition, temperature, on the performance of SOEC has been investigated systematically. The SOEC with 10 μ m air electrode thickness, functional layer, fuel electrode having 20 vol% PMMA content, addition of YSZ-GDC adhesion layer gives the better performance in overall results and the voltage obtained for this SOEC at current density of 0.8 A.cm −2 is ∼1.25 V at 800°C in 49% N2, 5% H2, 23% CO2 and 23% H2 O gas mixture at fuel electrode side. To identify the electrochemical processes occurring at the electrodes of SOEC, distribution function of relaxation time (DRT) analysis of the electrochemical impedance (EIS) data is carried out.